Role and Contribution of Pokhara's Civil Society in the People's Movement of 2005/2006 - Bhandari, Arjun Bahadur (HISAN: Journal of History Association of Nepal, 2022)
The people of Nepal have made numerous sacrifices and engaged in various democratic movements and armed conflicts in order to achieve democracy in the country. These efforts have been successful, and Nepal is now a federal democratic republic. In the past, Nepal was ruled by a centralized monarchy, but this changed in 1950 with the Movement for democracy. However, the elected Nepali Congress government was not able to effectively address the people's needs, and King Mahendra's ambition led to the implementation of the autocratic Panchayat system in 1990. This system was eventually replaced with a multi-party democracy and constitutional monarchy in 1990, but the people were dissatisfied with the parties' governing style and the 2001 Royal massacre and King Gyanendra's ambition led to the country being ruled directly by the King. The Maoist insurgency fought for the political rights and socio-economic uplift of the people, but it was the 2005/2006 civilian movement, led by civil society, that had the greatest impact on the country. This research studies the role and contribution of Pokhara's civil society in the 19-day movement of 2006, which aimed to bring about political change and overthrow the autocracy, and its impact on Nepal.